Seismic Deformation and Stability of Earth Dams: A Comprehensive ‎Review with an Application to Iraq (Journal of University of Babylon for Engineering Sciences, 2026)
Seismic action can seriously endanger hydraulic infrastructure, particularly in areas where large water-retention dams are built on the ground characterized by complex geotechnical conditions. Iraq, situated near the tectonically active Zagros-Bitlis seismic belt, has several strategic earth dams whose response to high-level ground shaking is vital for regional water security and public safety. Despite significant progress in geotechnical and earthquake engineering, earth dams remain inherently vulnerable to seismic loading. Recent global and regional seismic events continue to demonstrate the limitations of current design and assessment approaches. Earth dams, whether natural or constructed from compacted soil materials, remain vulnerable. With Iraq's growing dependence on ageing dams like Mosul, Darbandikhan, Dokan, and Haditha, system-wide seismic assessments are vital. The paper presents a worldwide review of the seismic behavior of earth dams, and then relates it to the geological and seismic situation in Iraq. The report reviews recorded dam behaviour during past earthquakes to determine common failure modes, mechanisms of deformation, and controlling influences on seismic response. It examines analytical, empirical, and numerical techniques for estimating seismic deformation, ranging from simplified Newmark sliding‐block prescribing to sophisticated nonlinear effective stress finite-element analysis and finite difference models. Incorporating the international experience with local conditions, this article enables the engineers and researchers in Iraq to use a structured assessment tool of seismic deformation analysis through existing and newly constructed earth dams. The review emphasizes the significance of recently improved hazard analysis systems, full-scale material testing, and advanced state-of-the-art numerical modeling methods to tackle this pressing geotechnical engineering problem in Iraq.